Study of vitamin D deficiency and supplementation in pre-eclamptic toxemia & its feto-maternal outcome - Singh, Neetu; kumar, Dileep; Pandey, Kiran; Gupta, Neena; Balyan, Rashmi; Chandanan, Ani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The present study has been conducted to study the prevalence of vitamin D deficiency and evaluate the efficacy of vitamin D supplementation over pre-eclamptic women & its maternal and neonatal outcome. Methods: The present study was conducted on 280 pre-eclamptic women. In 2nd & 3rd trimester attending outpatient department at Upper India Sugar Exchange Maternity Hospital, Department of Obstetrics and Gynecology G.S.V.M. Medical college, Kanpur, during the period of January 2013 to July 2014.Vit D measured on first visit and supplementation of vitamin D 2000 IU per day accordingly .Patients were followed till delivery for antinatal and neonatal outcome. Results: Vitamin D supplementation had significant reduction in incidence of severe preeclampsia. Vitamin D supplementation had significant 1.4 times reduction in incidence of caesarian section (OR=3.659, 95% CI=1.3668 to 9.9745, P=0.01). Only 7.141% who received Vitamin D supplementation had new born with birth weight >2.5 kg in comparison to 26.67% pregnant women who did not received Vitamin D supplementation (OR=4.8431, 95% CI=1.6928-13.8561, P=0.0033). Conclusions: Vitamin D supplementation is significantly associated with better maternal and neonatal outcome.